Implementasi Program-Program Pembelajaran TK Unggulan di Surakarta - Wardhani, Junita Dwi; Prasetyarini, Aryati; Astuti, Wili (Universitas Muhammadiyah Surakarta, 2014)
The aim of this research is to assess the learning program on TKIU Al Khoir Surakarta for academic year 2010-2011. The problem is how the Montessory learning method implemented at TKIU Al Khoir. The research methodology used is a qualitative approach in the form of the naturalistic and a purposive sampling. The data sources in this research include information about the program of instruction in kindergarten the flagship. The Data in the form of words were taken from three sources: events, informants and documents. Data collection techniques used in research are observations, interviews and document analysis. Results of investigation showed TKIU Al Khoir well using integrated curriculum including approaches such as a thematic approach, there is engineering a learning environment, learning objectives focussing on moral development, reading a written/material goods, the role of students as a learning object, a gaming device is limited, a library with classrooms, and a new limited role parents financially.